Thermal performance of public courtyards in Yazd, Iran during summer - Hariri, Ali Sadeghi (2012)
The cities located in the hot and dry regions are characterized by the intense solar radiation and having two extremely opposite hot summer and cold winter. The traditional architecture of this region demonstrates that the compactness in the urban form while having some open spaces like the courtyard is the best answer to this extreme climate. In the case of Yazd city, a unique public courtyard pattern surrounded with colonnades is identified in the historical area as the main solution for building urban open spaces in the past. But the contemporary urban design disregards the traditional solution due to the need to include vehicular traffic and a greater degree of activity to support social urban life. The aim of this research is to study the effects of courtyard form on its thermal environment by focusing on the role of solar radiation in Yazd during summer. The study uses ENVI-met® which is a computational climatic modeling tool that simulates the microclimatic changes within the urban environment. The effects of courtyard design parameters of orientation, size, aspect ratio H/W and colonnade aspect ratio h/w on outdoor thermal environment are evaluated in this research. Ten square shape courtyard models are simulated to assess the effects of design parameters on air temperature Ta, air humidity RH, wind speed WS and mean radiant temperature Tmrt as well as thermal index of predicted mean vote PMV. A field measurement of air and globe temperature is also conducted in an existing public courtyard in order to be compared with the result of computer simulation. The results show the courtyard space can decrease the Tmrt up to 40°C and the PMV value up to 2.5 in shaded area compared to unobstructed area. A comparison of all experimental models reveals that the thermal intensity and the amount of sunlit areas inside a courtyard strongly depends on courtyard orientation, aspect ratio H/W and the colonnade aspect ratio h/w. It is also found that the direct solar radiation and its resulted Tmrt are the primary indicator of outdoor thermal environment in hot and dry climate of Yazd during summer day. The study concludes that creating comfortable thermal environment in outdoor spaces in hot and dry climate is beyond the reach of any architectural design using passive strategies. However, mitigating the extreme heat of the summer through a careful combination of courtyard design parameters is possible. The strong cooling effect of colonnades surrounding a courtyard is also highlighted by this research. This study contributes new architectural knowledge for the architects to design more thermally comfortable public courtyards in hot and dry climate. The future researches can look forward to test the applicability of the study‟s findings in the winter condition as the thermal comfort is needed through the whole year and in all spaces.